Characterization of tissue scaffolds for time-dependent biotransport criteria – a novel computational procedure. Issue 11 (17th August 2016) - Li, Eric; Chang, C.C.; Zhang, Zhongpu; Li, Qing
Abstract: This study aims to establish a new computational framework that allows modeling transient oxygen diffusion in tissue scaffolds more efficiently. It has been well known that the survival of cells strongly relies on continuous oxygen/nutrient supply and metabolite removal. With optimal design in scaffold architecture, its ability to sustain long distance oxygen supply could be improved considerably. In this study, finite element based homogenization procedure is first used to characterize the initial effective biotransport properties in silico . These initial properties are proper indicators to prediction of the on-going performance of tissue scaffolds over time. The transient model by adopting an edge-based smoothed finite element method with combination of mass-redistributed method is then established to more efficiently simulate the transient oxygen transfer process in tissue scaffolds. The proposed new method allows large time steps to model the oxygen diffusion process without losing numerical accuracy, thereby enhancing the computational efficiency significantly, in particular for the design optimization problems which typically require numerous analysis iterations. A number of different scaffold designs are examined either under net diffusion without cell seeding, or under cellular oxygen/nutrient uptake with or without considering cell viability. The association between the homogenized effective diffusivity of net scaffold microstructures and corresponding transient diffusion and time-dependent cellular activities is divulged. This study provides some insights into scaffold design.